Exploring sustainability in social welfare non-governmental organisations - Ruzaini Ijon,; Azlinda Azman,; Paramjit Singh Jamir Singh, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Non-governmental organisations are acknowledged for their contributions by playing a vital role in promoting social justice and human rights, advocating for marginalised groups, and empowering them to voice their concerns. NGOs collaborate with both the government and private sector. NGOs enable communities to engage in decision-making processes. Additionally, they often work on the ground, providing direct support and resources to communities in need, thereby addressing immediate needs and working towards long-term solutions. They are critical in achieving sustainable development goals, like improving health and eradicating poverty. Despite the advantages, there is uncertainty because aspects of their sustainability have yet to be thoroughly studied, especially in the Malaysian context. This study was therefore carried out to evaluate the study objectives and determine whether the interview questions were appropriate. This study used an entirely qualitative method. Two staff members from one social welfare NGO were interviewed. The results reveal that the interview questions were appropriate for the study objectives, with some corrections needed. The corrections required were primarily in the wording and clarity of the questions, but overall, the qualitative method effectively gathered relevant information from the staff.